Idaho Commission selecting site for Idaho State Building, Alaska Yukon Pacific Exposition, Seattle, Washington, March 1909 - Nowell, Frank H., 1864-1950 (1909)
On verso of image: Idaho Com. 3/19/09. Gov. Brady [James H.], second from left. Caption on image: x578 Also shows: John Edward Chilberg and Ira A. Nadeau PH Coll 727.21 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number